A new approach for measuring surface hydrological connectivity. Issue 3 (29th October 2019) - Wolstenholme, Joshua M.; Smith, Mark W.; Baird, Andy J.; Sim, Thomas G.
Abstract: The development of surface hydrological connectivity is a key determinant of flood magnitude in drylands. Thresholds in runoff response may be reached when isolated runoff‐generating areas connect with each other to form continuous links to river channels, enabling these areas to contribute to flood hydrographs. Such threshold behaviour explains observed nonlinearities and scale dependencies of dryland rainfall–runoff relationships and complicates attempts at flood prediction. However, field methods for measuring the propensity of a surface to transmit water downslope are lacking, and conventional techniques of infiltration measurement are often inappropriate for use on non‐agricultural drylands. Here, we argue for a reconceptualization of the dryland surface runoff process, suggesting that the downslope transfer of water should be considered alongside surface infiltration; that is, there is a need for the "aggregated" measurement of infiltration and overland flow hydraulics. Surface application of a set volume of water at a standardized rate generates runoff that travels downslope; the distance it travels downslope is determined by infiltration along the flow, integration of flow paths, and flow resistance. We demonstrate the potential of such a combined measurement system coupled with structure‐from‐motion photogrammetry to identify surface controls on runoff generation and transfer on dryland hillslopes, with vegetation, slope, surface stone cover, and surface roughness all having a significant effect. The measurement system has been used on slopes up to 37° compared with the flat surface typically required for infiltration methods. On average, the field workflow takes 10–15 min, considerably quicker than rainfall simulation. A wider variety of surfaces can be sampled with relative ease, as the method is not restricted to stone and vegetation‐free land. We argue that this aggregated measurement represents surface connectivity and dryland runoff response better than standard hydrological approaches and can be applied on a much greater variety of dryland surfaces. Abstract : Infiltration methods used in dryland environments are reviewed, and a new method is proposed to better represent hydrological processes. It is a simple aggregate measure of infiltration and overland flow combined with Structure‐from‐Motion.